Structure of the ligand-binding domain of oestrogen receptor beta in the presence of a partial agonist and a full antagonist. - Pike, A; Brzozowski, A; Hubbard, R; Bonn, T; Thorsell, A; Engström, O; Ljunggren, J; Gustafsson, J; Carlquist, M (1999)
Oestrogens exert their physiological effects through two receptor subtypes. Here we report the three-dimensional structure of the oestrogen receptor beta isoform (ERbeta) ligand-binding domain (LBD) in the presence of the phyto-oestrogen genistein and the antagonist raloxifene. The overall structure of ERbeta-LBD is very similar to that previously reported for ERalpha. Each ligand interacts with a unique set of residues within the hormone-binding cavity and induces a distinct orientation in the AF-2 helix (H12). The bulky side chain of raloxifene protrudes from the cavity and physically prevents the alignment of H12 over the bound ligand. In contrast, genistein is completely buried within the hydrophobic core of the protein and binds in a manner similar to that observed for ER's endogenous hormone, 17beta-oestradiol. However, in the ERbeta-genistein complex, H12 does not adopt the distinctive 'agonist' position but, instead, lies in a similar orientation to that induced by ER antagonists. Such a sub-optimal alignment of the transactivation helix is consistent with genistein's partial agonist character in ERbeta and demonstrates how ER's transcriptional response to certain bound ligands is attenuated.